Workshop on Interactive Systems in Healthcare - Hayes, Gillian; Tan, Desney ((2010) Organizers: Invited Workshop at CHI 2010 Conference on Human Factors in Computing Systems, 2010)
The Workshop on Interactive Systems in Healthcare (WISH) will take place Sunday, April 11th, 2010 in conjunction with the ACM CHI 2010 Conference on Human Factors and Computing Systems, at the CHI conference site, the Hyatt Regency in Atlanta, Georgia, USA. The workshop is open to all CHI attendees. To attend, please register separately for the workshop. When you register for CHI, add WISH as a one day workshop. If you've already registered for CHI, you can log back in to the registration site and add the workshop to your program. WISH will be an event-filled workshop lasting the entire day. See the program for more details.